#TITLE_ALTERNATIVE# - DAMAYANTI (NIM.15311060), HAPSARI
Brackish water treatment was investigated with ion exchange method using cation exchange resin (H+) and anion exchange resin (OH- form). The objective of this study is to determine the capacity of resin to remove major cation (Na+ and Ca2+) and major anion (Cl- and SO42-), as well as determine the design criteria applicable with the composition of water according to the characteristic of brackish water sample taken in North Jakarta coastal area. Single component isotherm adsorption analysis using artificial water showed that Langmuir and Freundlich model were fitted the data. From pH variation experiment, given that removal and adsorption capacity for both anion increased through the decline of pH (optimum in pH 6 with value of Cl- 2,73 meq Cl-/g resin and SO42- 4,21 meq SO42- /g resin), but both cation adsorption capacity increased in more alakis pH (optimum in pH 8 value of Na+ 2,52 meq Na2+/g resin and Ca2+ 2,6 meq Ca2+/g resin). Resins bed height directly proportional with the amount of resin used and water volume treated, but could inrease or decrease the adsorption capacity. From all of preliminary studies using artificial water, adsorption capacity for Na+, Ca2+, Cl-, and SO42- in range of 1,09 – 2,52 meq Na2+/g resin, 1,48 – 3,15 Ca2+/g resin, 1,89 – 3,9 meq Cl-/g resin, and 1,38 – 4,21 meq SO42- /g resin, respectively. Main study using original brackish water showed that column (breakthrough) capacity for cation resin is 0,716 meq/g resin and column capacity for anion resin is 0,615 meq/g, giving applicable reactor column dimension is 47,8 cm x 71,7 cm. The adsorption for ion exchange technology was fast and resulted in a big adsorption capacity, making this technology a good candidate of Na+, Cl-, Ca2+, and SO42 removal